Factor Mobility and Fiscal Policy in the EU: Policy Issues and Analytical Approaches - David E. Wildasin (Center for Economic Studies and ifo Institute (CESifo), 2000)
Increased integration of labour and capital markets creates significant challenges for the welfare states of modern Europe. Taxation of capital and labour that finances extensive programs of cash and in-kind redistribution creates incentives for capital owners and workers to locate in regions where they obtain favorable fiscal treatment. Competition among countries for mobile resources constrains their ability to alter the distribution of income and may lead to reductions in the size and scope of redistributive policies. Mobility of labour and capital is imperfect, however. Recent trends indicate that labour and capital are neither perfectly mobile nor perfectly immobile, but rather adjust gradually to market conditions and economic policies. This paper presents an explicitly dynamic analysis showing that governments can achieve some redistribution when it is costly for factors of production to relocate. As the costs of factor mobility fall, however, the effectiveness of redistributive policies is more limited, and governments have weaker incentives to pursue them. Liberalised immigration policies, EU enlargement, and other steps that promote integration of the factors markets of Western Europe with those of surrounding regions thus present a challenge to policymakers if they also wish to maintain fiscal systems with extensive redistribution.
Keywords: G10; H00; J60; 330